Pilot test of intranasal oxytocin as an enhancer of brief couples therapy for posttraumatic stress disorder. (May 2023) - Sippel, Lauren M.; Khalifian, Chandra E.; Knopp, Kayla C.; Webster, Katelyn; Maglione, Jeanne; Holcomb, Julie; Flanagan, Julianne C.; Monson, Candice M.; Holtzheimer, Paul E.; Morland, Leslie A.
Abstract: Posttraumatic stress disorder (PTSD) negatively impacts military veterans and their intimate partners. Cognitive-Behavioral Conjoint Therapy (CBCT) was developed to address both PTSD and relationship satisfaction among couples. Although efficacious in improving PTSD, the effects of CBCT and the 8-session brief CBCT (bCBCT) on relationship satisfaction among veteran patients with PTSD are modest. Pharmacological augmentation with the neuropeptide oxytocin is promising for enhancing bCBCT's potency due to its effects on mechanisms of trauma recovery (e.g., extinction learning) and relationship functioning (e.g., trust, communication). The goal of this pilot uncontrolled clinical trial was to examine the feasibility and preliminary efficacy of bCBCT augmented with intranasal oxytocin for improving PTSD and relationship satisfaction among 10 U.S. veterans with PTSD and their intimate partners. Veterans self-administered 40 international units of intranasal oxytocin 30 min before each bCBCT session delivered to the couple via telehealth. Both partners completed pre-assessment, weekly, post, and 3-month follow-up assessments of PTSD symptoms and relationship satisfaction. Couples also provided qualitative feedback related to feasibility and engagement. Nine dyads completed the treatment. There were no serious adverse events. Veterans and partners reported moderate to large effect size improvements in relationship satisfaction (Hedge's g  = 0.55 and 1.01, respectively). Veterans reported large effect size reductions in PTSD severity (Hedge's g  = 1.87). These results suggest that virtual oxytocin-assisted bCBCT is feasible, scalable, potentially efficacious, and should be tested with a placebo-controlled randomized controlled trial. Highlights: Intranasal oxytocin could boost effects of couples therapy for PTSD. This open trial is the first to augment couples therapy for PTSD with oxytocin. 9 of 10 couples completed the treatment with no serious adverse events. Veterans self-reported large improvements in PTSD symptoms. Dyads reported moderate-to-large improvements in relationship satisfaction.